Wastewater Characterization of Selected Industries in Quaid-e-Azam Industrial Estate: Treatment Options and Impact on Groundwater Quality: Treatment Options and Impact on Groundwater Quality - Haydar, Sajjad; Hussain, Ghulam; Haider, Husnain; Attiq-ur-Rehman (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
This research was carried out to characterize the wastewater of major industries of Quaid-e-Azam Industrial Estate (QIE), to analyze effect of wastewater drain on groundwater quality in the area, and to suggest appropriate wastewater treatment option(s) for QIE. Composite wastewater samples were collected and analyzed for pH, temperature, biochemical oxygen demand (BOD), filtered BOD (F-BOD), chemical oxygen demand (COD), filtered COD (F-COD), total Kjeldahl nitrogen (N), total suspended solids (TSS),total dissolved solids (TDS), sulphates, chromium (Cr), lead (Pb), cadmium (Cd) and copper (Cu). Results showed that BOD, COD, TSS, TKN, Pb and Cd exceeded the limits of National Environmental Quality Standards Furthermore, groundwater samples were collected from selected tube wells in near vicinity of QIE and analyzed for pH, nitrates, total hardness, TDS, turbidity, sulphates, Pb, Cd, Cr and Cu. The results showed that groundwater contamination with Pb, Cd, and Cr due to unlined industrial drain.